A Mixed Phytogenic Modulates the Rumen Bacteria Composition and Milk Fatty Acid Profile of Water Buffaloes - Hassan, Faiz-ul; Ebeid, Hossam M.; Tang, Zhenhua; Li, Mengwei; Peng, Lijuan; Peng, Kaiping; Liang, Xin; Yang, Chengjian (Frontiers in Veterinary Science, 2020)
This study was aimed to evaluate the effect of a mixed phytogenic (MP) on rumen bacteria and their potential association with rumen fermentation and milk yield parameters in water buffaloes. Twenty Murrah buffaloes were fed a basal diet (consisting of maize silage, brewers’ grains, and concentrate mixture) for 6 weeks supplemented with 0 (control), 15 (MP15), 25 (MP25), and 35 (MP35) g of mixed phytogenic/buffalo per d. The mixed phytogenic contained fennel (seeds), ajwain (seeds), ginger (tubers), Swertia chirata (leaves), Citrullus colocynthis (fruit), turmeric, fenugreek (seeds), Terminalia chebula (fruit), licorice (roots) and Phyllanthus emblica (fruit) in equal quantities. After two weeks of adaptation, daily milk yield, and weekly milk composition were recorded. On the last day of the experiment (d 42), rumen contents were collected to determine rumen fermentation parameters and bacterial diversity through 16S rRNA sequencing. Results revealed no change in dry matter intake, milk yield and rumen fermentation parameters except pH, which increased (P=0.029) in response to MP supplementation. The mixed phytogenic increased (P < 0.01) milk fatty acids (C4 to C14:0) in MP15 only. The milk C16:1 content and its unsaturation index were higher (P < 0.05) in MP35 as compared to the control and other treatments. Furthermore, C18:3n3 was higher (P < 0.05) in the control, MP15, and MP25, as compared to MP35. Supplementation of MP tended to increase (P = 0.095) the Shannon index of bacterial diversity and a difference (P < 0.05) among treatment groups was observed in beta diversity. Feeding MP increased the Firmicutes, Proteobacteria, and Spirochaetes but decreased Bacteroidetes numerically. In addition, the dominant genus Prevotella decreased in all treatment groups while Pseudobutyrivibrio, Butyrivibrio, and Succinivibrioanceae increased numerically in MP25 and MP35. The mixed phytogenic promoted groups of rumen bacteria positively associated with milk and fat yield. Overall, our study revealed 14 positive correlations of rumen bacteria with milk yield and eight with rumen fermentation parameters. Our findings reveal substantial changes in the rumen bacteriome composition and milk fatty acid content in response to MP but these results should be interpreted carefully, as the sample size of our study was relatively small.